Pengaruh Disiplin Kerja dan Keselamatan Kesehatan Kerja (K3) Terhadap Kinerja Karyawan Harian pada PT. Nico Jaya Pratama Kab. Karawang - Vidia Nur Fauziah; Budi Rismayadi; Wike Pertiwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research was conducted at PT. Nico Jaya Pratama Karawang. The aim of this research is to determine the influence of work discipline and occupational health and safety (K3) on daily employee performance at PT. Nico Jaya Pratama, Karawang Regency, both partially and simultaneously. The population in this study was 50 daily employees. The sampling method in this research uses a saturated sample or census. The data used is primary data and secondary data. The data analysis method used is the multiple linear regression method. The research results show that work discipline partially influences the daily performance of employees at PT. Nico Jaya Pratama. Occupational safety and health (K3) partially influences daily employee performance at PT. Nico Jaya Pratama. Simultaneously work discipline and occupational safety and health (K3) have an influence on daily employee performance at PT. Nico Jaya Pratama. The great influence of work discipline and occupational safety and health (K3) on daily employee performance is shown by the coefficient of determination of 0.355. This shows that 35.5% of employee performance is influenced by work discipline and occupational safety and health (K3) and the remaining 0.645 or 64.5% is influenced by other variables not used in this research.